Beach pollution from marine litter: Analysis with the DPSIR framework (driver, pressure, state, impact, response) in Tuscany, Italy. (October 2022) - Federigi, Ileana; Balestri, Elena; Castelli, Alberto; De Battisti, Davide; Maltagliati, Ferruccio; Menicagli, Virginia; Verani, Marco; Lardicci, Claudio; Carducci, Annalaura
Graphical abstract: Highlights: DPSIR applied to beach contamination through data search and fieldwork. Fieldwork allowed to gain insight into local pressures, state, and health impact of beach-stranded. Main local responses: waste removal from drainage system and recycling of stranded material. Local and regional efforts are required to build a systemic view of beach contamination. Abstract: Beaches are affected by the accumulation of natural and anthropogenic material; however, this environmental issue has not yet been explored from a One Health perspective. In this paper, the conceptual framework of DPSIR (Drivers-Pressures-State-Impact-Response) was used to understand the beach-stranded material issue in a systemic way and a data-based classification for some environmental indicators was developed to support the DPSIR analysis. The model was applied to an Italian coastal municipality as a case study, through the collection of data from a variety of data sources: publicly accessible database, data from a stakeholders' network (i.e., coastal authority, solid waste company, sewerage company, drainage consortium), and fieldwork consisting in microbiological analysis of stranded material and underlying sand, visual census of macrolitter along beach and waterways. In the study area, solid wastes production was a high pressure (768 kg/capita/year), but in situ visual observations of floating wastes at the outlet of the canals revealed that the contribution of local waterways to marine litter was negligible, thus suggesting the effectiveness of the measures adopted along local waterways by the drainage consortium (i.e., grids at the drainage pumping stations). Nevertheless, very high quantity of anthropogenic wastes was counted during the beach litter surveys (603 items/100 m), probably as a result of coastal current pathway that transported material from major watercourses (>100 km 2 drainage basin size; 23 items/h). On the contrary, local sewage production represented a very high pressure (>33, 000 m 3 /km) that impacted on the microbiological quality of the stranded material with moderate to high level of fecal bacteria indicators detected in the beach cast. The underlying sand was affected by such contamination, with most of the sample within the provisional limit set by WHO for enterococci in beach sand (60 CFU/g) that was associated to a health risk of<5 % of gastroenteritis attributable to accidental ingestion of sand; nevertheless, some enterococci peak values (980 MPN/g) could be associated to a health risk for gastroenteritis>10 %. The beach-stranded material was collected without separating the sand, with annual quantity of 1, 243 kg/m, that was processed in a dedicated facility allowing to recover up to 98 % of sand and biomass after the treatment, with moderate expenditure for the coastal municipality (22 €/m). Overall, this study allowed to better figure out the cause-effect relationships underlying the accumulation of stranded material along shoreline and the effectiveness of the management practices toward beach-stranded material. Therefore, the usage of the DPSIR framework as structuring model to understand the problem of stranded material could be useful for beach managers and administrators, and its adoption within beach management programs is worth for improving beach quality.